Experimental and numerical investigation of gas-liquid metal two-phase flow pumping. (May 2021) - Rosettani, Josh; Ahmed, Wael; Geddis, Philip; Wu, Lijun; Clements, Bruce
Abstract: Adapting an efficient method for pumping gas-liquid metal two-phase flow can make liquid metal magnetohydrodynamics (LMMHD) power generation systems economically feasible. An experimental facility was developed using a dual injection gas-lift pump to provide the circulation needed for the liquid metal in the LMMHD system. Also, a numerical simulation was performed in order to understand the behaviour of the two-phase flow through the gas-lift pump and be able to optimize the pump design for the best operational condition of the LMMHD system. In addition, the data were compared to a 1-D drift flux model that predicted the performance of the pump within the loop. The numerical results were found to be in an agreement with the experiments within ±25% which is considered adequate for optimization and design purposes of a two-phase flow system. The dual injection design was evaluated, and the axial injection mode was found to be more efficient in providing the required pumping than radial mode. Moreover, the flow visualization of the two-phase flow patterns seen in the pump riser was captured both experimentally and numerically indicating a swirl-like motion that can potentially be used to enhance heat transfer in the actual operational setting. Also, the optimum condition for pumping was found to occur at a slug-like flow structure in the riser.